In a Crackdown on ‘Illicit’ Antiquities, the Manhattan District Attorney Seizes 6 Statues From Phoenix Fine Art - Henri Neuendorf (Les Carnets de l’ACoSt)
A report appeared in artnet News on January 11, 2018, concerning six Greek terracotta artifacts of illicit provenance, of which four are figurative terracottas of the sixth century B.C.E.